Meditation and Mind-Body Practices: Effects on Brain-derived Neurotrophic Factor and Brain Health: A Narrative Review - Giridharan, Selvaraj; Pandiyan, Bhuvana (International Research Journal of Ayurveda & Yoga, 2025)
Background: Brain-derived neurotrophic factor (BDNF) plays a crucial role in neuroplasticity and cognition. Meditation and mind-body exercises such as yoga may increase BDNF levels, offering a non-pharmacological strategy to enhance brain health. Methods: This narrative review synthesizes evidence from published studies, primarily randomized controlled trials, sourced from PubMed, Scopus, Cochrane Library, and Web of Science, between 2020 and 2025, in accordance with the PRISMA guidelines. Studies have focused on meditation and mind-body interventions and their effects on peripheral BDNF levels. Results: Eight studies demonstrated that mindfulness-based interventions, including yoga and meditation, consistently elevated BDNF levels across diverse populations, including healthy adults and individuals with depression. These increases are linked to reduced stress and inflammation, suggesting the underlying mechanisms. Mental health benefits, such as reduced depression and anxiety, have been widely observed, although cognitive and functional outcomes vary, particularly in older adults, where some studies have noted BDNF attenuation. Conclusion: Meditation and mind-body practices have the potential to enhance BDNF levels and improve mental health, with possible cognitive benefits. However, inconsistencies in older adults and chronic pain populations underscore the need for fur